2014
DOI: 10.1111/1754-9485.12208
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy in the Barwon South Western Region: A rural perspective

Abstract: Introduction: Cancer-related mortality rates are higher in rural areas compared with urban regions. Whether there are corresponding geographical variations in radiotherapy utilisation rates (RURs) is the subject of this study. Methods: RURs for the regional centre of Geelong and rural areas of the Barwon South Western Region were calculated using a population-based database (2009). Results: Lower RURs were observed for rural patients compared with the Geelong region for prostate cancer (15.7% vs 25.8%, P = 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…This is reflected in the report by the National Radiotherapy Advisory Group in England, which proposed that all patients should live within a 45 min travel time of their nearest centre [12,13]. A recent Australian study showed lower radiotherapy utilisation in rural Victoria (no local radiotherapy services) compared with an urban location with local radiotherapy [14]. This is consistent with findings of other contemporary studies from the UK, Europe, New Zealand and North America, which have reported relationships between availability of local radiotherapy services and radiotherapy utilisation [15e25].…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected in the report by the National Radiotherapy Advisory Group in England, which proposed that all patients should live within a 45 min travel time of their nearest centre [12,13]. A recent Australian study showed lower radiotherapy utilisation in rural Victoria (no local radiotherapy services) compared with an urban location with local radiotherapy [14]. This is consistent with findings of other contemporary studies from the UK, Europe, New Zealand and North America, which have reported relationships between availability of local radiotherapy services and radiotherapy utilisation [15e25].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study on NSW and factors that influence RT, multiple barriers were identified and perceived by health professionals as well as consumers, including the availability of local RT services, finding suitable accommodations, travel, anxiety, fear of the city and isolation . RT use rates are lower in prostate cancer, rectal cancer, lymphoma and all cancers, overall, as indicated by a study from the Barwon South Western region …”
Section: Introductionmentioning
confidence: 99%
“…9 RT use rates are lower in prostate cancer, rectal cancer, lymphoma and all cancers, overall, as indicated by a study from the Barwon South Western region. 10 Funding for and establishing regional cancer centres in Australia have significantly increased in recent years, which provides regional and rural patients with the opportunity for treatment closer to home with, generally, more family and social support as well as convenience. Head and neck cancer patients require regular follow up after treatment is completed, and certain patients require hospital admission during and after treatment because of side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Access to radiotherapy facilities has historically been a significant challenge for patients living in regional and rural Australia. Whilst urban populations have enjoyed relatively easier access, those living more distantly from facilities have experienced a lower utilisation rate of radiotherapy (RT) services, with poorer survival from prostate and rectal cancer for rural populations . Complex cultural issues impact highly on the attendance of Indigenous patients for diagnosis, and at cancer treatment centres, with substantial barriers in accessing care …”
Section: Introductionmentioning
confidence: 99%